ROLE OF HOMOEOPATHIC REMEDY AMYL NITROSUM IN THE MANAGEMENT OF ESSENTIAL HYPERTENSION-CASE SERIES - Dr. Jyoti A moolabharati,; Dr. DR MUNJAL THAKAR,; Dr. Poorav Desai, (The Bioscan, 2025)
Hypertension is a common life style disorder and is a very strong risk factor for cardiovascular diseases (CVDs). It is estimated that it increases the risk at least two-fold for CVDs including coronary artery disease (CAD), congestive heart failure/stroke, renal failure and peripheral arterial disease. Hypertension is defined as elevated blood pressure where systolic blood pressure is greater than 140 mmHg and diastolic pressure is greater than 90 mmHg or greater or any level of blood pressure in patient taking antihypertensive medications. Essential hypertension is a common cardiovascular disorder often associated with headache, palpitations, giddiness, and exertional fatigue. Homoeopathy has been explored as a supportive approach in its management.